China Pakistan Economic Corridor (CPEC): Analysis of Internal and External Challenges - Ashraf, Maryum; Shafiq, Awaisra; Batool, Sana (International Journal of Business, Economics and Management, 2017)
China Pakistan Economic Corridor (CPEC) is a comprehensive development strategy that not only causes to economic and social environment in two countries but also has potential of incorporation with other sub-regions of Asia. It is like a game changer project which could transform the fate of Pakistan. It helps to improve the trade, infrastructure, and enhance regional connectivity. Despite these opportunities there exist several internal and external challenges for the government of Pakistan to implement this multidimensional project. The study is organized to analyze some internal and external challenges for Pakistan that are associated with the implementation of CPEC project.